Current Practice for Management of Otitis Media with Effusion in Children – A Review - Santosh K. Swain; Debasmita Dubey (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: A common childhood disease known as otitis media with effusion (OME) is described as the presence of fluids in the middle ear without any features of an acute ear infection. OME in the pediatric age group often leads to manifestations of hearing loss and speech delay. Methods: The search for recent research articles on managment of otitis media with effusion was done with databases scopus, pubMed, medline, and google scholar. This review article discusses the epidemiology, etiopathogenesis, clinical features, and current management of OME in children. Results: Nasal balloon auto-inflation appears to be a promising technique with some benefits in selected cases of OME. Insertion of grommets or ventilation tubes in pediatric patients with OME and hearing impairment is helpful in case of failed watchful waiting. Grommet insertion is usually effective in restoring hearing thresholds. Adenoidectomy can be performed in addition to grommet insertion in children of OME with adenoid hypertrophy. A combination of ventilation tubes and adenoidectomy is broadly helpful to normalize the hearing and increasing nasal patency. Early treatment of OME is helpful to improve the quality of life and social and educational performance. Neither medical treatment nor complementary or alternative treatment has been proven for giving effective treatment of OME. In children of OME with hearing impairment benefit through the effective restoration of hearing by insertion of ventilation tubes (grommets). Adenoidectomy is helpful in the case of persistent OME. Conclusion: The combination of ventilation tubes and adenoidectomy in children with OME is beneficial in terms of hearing, respiratory, and development of the children.